(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت هذه الدراسة إلى معرفة أثر تنشيط المبيعات في قيمة العلامة التجارية لدى العميل, وتحديد أثر تنشيط المبيعات في كل بعد من أبعاد قيمة العلامة التجارية لدى العميل. وقد دُرس مستهلكو العلامات التجارية الوطنية للملابس الجاهزة في محافظة اللاذقية. وتوصلت الدراسة إلى أن تنشيط المبيعات يؤثر في قيمة العلامة التجارية لدى العميل, إذ إن هناك علاقة إيجابية بين تنشيط المبيعات, وقيمة العلامة التجارية لدى العميل، وأنّ أكثر بعد من أبعاد قيمة العلامة التجارية لدى العميل تأثراً بتنشيط المبيعات هو الولاء للعلامة التجارية. The purpose of this research is to investigate the Sales Promotion effects on Customer-based Brand Equity and to determine Sales Promotion influence on each dimension of Customer-based Brand Equity. National Brands of ready-made clothes consumers in Lattakia were studied. The study results shows that Sales Promotion affects Customer-based Brand Equity, and there is positive relationship between Sales Promotion and Customer-based Brand Equity. The most influenced dimension of Customer-based Brand Equity by Sales Promotion was customer loyalty.